STUDENTS WITH A MIGRANT BACKGROUND: POSSIBILITIES AND PROBLEMS OF THEIR INTEGRATION INTO EDUCATION SYSTEM - Stasiūnaitienė, Eglė; Nedzinskaitė-Mačiūnienė, Rasa; Mazlaveckiene, Gerda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This paper examines the integration of students with a migrant background and the problems encountered by the teachers, who seek for their successful integration via the educational process. A qualitative approach has been chosen for the research. On the basis of a semi-structured interview (N=12), it is proposed that despite the existing migrant policy, there are still urgent demands from teachers to get specific methodology of working with students from migrant backgrounds. Moreover, the school administration and teachers often have to search for optimal and individual decisions to ensure the process of integration. The most frequently used means of ensuring children’s integration into the educational process include individual education plans, non-formal activities, tutoring in the Lithuanian language, as well as application of the support model for individual student(s). Finally, parent involvement into the processes of children’s education and integration could be more active, yet they themselves often need a lot of support.